Politeness and Transitivity Strategies in Speech Siraj Season 4 Arabic Cartoon Series Characters: Analysis Pragmatic Functional - Istiqomah, Salma Nur; Al Farisi, Mohamad Zaka; Langguly, Azra Adrina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines politeness strategies and transitivity patterns in the speech of the characters of the Arabic cartoon series Siraj Season 4 using a pragmatic functional approach. The background of the study departs from the limitations of studies that integrate Brown & Levinson's politeness theory with Systemic Functional Linguistics in Arabic children's media discourse. The purpose of this study is to describe the types of politeness strategies and types of transitivity processes that realize interpersonal meaning in the characters' speech. The study uses a qualitative descriptive method based on content analysis with data taken through purposive sampling from eleven episodes of Siraj. The analysis is carried out through the classification of politeness strategies (positive, negative, off record, and bald on record) and the identification of types of transitivity processes (material, mental, verbal, relational). The results show that positive and negative strategies are the most dominant, realized through mental and verbal processes that emphasize empathy, cooperation, and social respect. Meanwhile, off record strategies appear in educational contexts that emphasize moral gentleness. This study confirms that politeness in Siraj is a pragmatic and grammatical phenomenon that functions to educate socio moral values, and has implications for the development of Arabic language learning that emphasizes polite and reflective communication. Suggestions for future research include conducting comparative studies with other Arabic language children’s cartoons to reveal cross cultural differences in the realization of politeness strategies and transitivity patterns, as well as further developing the analysis by incorporating other meta functions within the Systemic Functional Linguistics framework.